RANCANG BANGUN SISTEM INFORMASI ADMINISTRASI DESA BERBASIS WEB DENGAN PENDEKATAN WATERFALL: STUDI KASUS DESA NAGRAK - Hidayat, Fajar Syahrul; Hendriadi, Ade Andri; Ridha, Azhari Ali (Jurnal Ilmiah Informatika Global, 2025)
The use of information technology in village government is a solution to improve the quality and efficiency of public services. This study aims to design and build a web-based village administration information system in Nagrak Village to replace the manual system which is considered ineffective and inefficient in responding to community needs. The development method used is the Waterfall System Development Life Cycle (SDLC) model which consists of five stages: needs analysis, system design, implementation, testing, and maintenance. The results of the system design include main features such as login, registration, letter submission, status checking, and letter verification by the admin. This system is also equipped with an interface that is designed to be simple, responsive, and user-friendly to facilitate all levels of society, including lay users. Through UML modeling, including use case diagrams, activity diagrams, and sequence diagrams, the system flow is clearly visualized to describe the work process between actors in the system. The implementation of this system shows a significant increase in the speed of service, accuracy of administrative data, and transparency and accessibility of services. In addition, the system makes it easy for village officials to manage correspondence digitally. This study recommends further development in the form of a mobile application and integration of automatic notification features so that the system is more adaptive to community needs and is able to reach wider users in real time.